A Longitudinal Study of Misarticulations in Postoperative Cleft Palate Children with Adequate Velopharyngeal Function - MICHI, Ken-ichi; SUZUKI, Noriko; YAMASHITA, Yukari; IMAI, Satoko (Journal of Japanese Cleft Palate Association, 1989)
In order to clarify the frequency of occurrence and changes of various articulation disorders in cleft palate children, longitudinal observations were made of 31 postoperative cleft palate children who obtained adequate velopharyngeal function after early surgical repair of the palate. The results are as follows; 1. Eighteen of 31 cases (58 %) showed misarticulations after early surgical repair. The frequency of the misarticulation was highest in palatalized misarticulation (PM), followed by glottal stop (GS), nasopharyngeal misarticulation (NM) and lateral misarticulation (LM). 2. In five of 18 cases misarticulation improved spontenously at the conversational level. 3. The percentage of spontenous improvement was higher in GS and NM than PM, but it was not observed in LM. 4. The age of occurrence of spontenous improvement varied depending on the kinds of misarticulations. The age of spontenous improvernen tin GS and NM was between 3: 0 (years: months) and 3: 6, and it was consistent with the age of obtaining adequate velopharyngeal function. That of PM and NM associated with PM was between 4: 6 and 5: 6. 5. Two different processes were observed for the subjects whose PM was improved spontenously. One process showed improvement from the consonant level which was acquired early in phonological development, and from the syllable level to the conversational level by stages. The other process showed the changes of the place of articulation from the tongue dorsum to the tongue tip in all consonants which showed PM at same time. Although the former cases showed the typical dynamic palatogram (DP) patterns of PM whereby the posterior portion of the tongue dorsum contacts the posterior border of the hard palate at the moment of maximum contact, the latter cases showed the DP patterns whereby the whole tongue dorsum contacts the whole hard palate.